Encyclopedia of Indian philosophies; Vol VII Abhidharma Buddhism to 15 A. D. - Potter, Karl.H (ed.); Jaini, Padmanabh S. (ed); Buswell, Robert E. (ed); Potter, Karl.H (ed.) (Delhi Motilal Banarsidas, 2011)
Introduction